Being Muslim in Soviet Central Asia, or an Alternative History of Muslim Modernity - Khalid, Adeeb (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2007)
AbstractThe literature on Muslim modernity takes little account of the experience of the Muslim societies of the Soviet Union, even though they might have undergone some of the most radical transitions to modernity. The Soviet sought a different kind of modernity, one without markets and liberalism, and one with little place for religion in it. I argue that the Soviet project succeeded to a great extent. This article explores some of the implications for our understanding of Muslim modernity if we are to take the experience of Soviet Muslim societies seriously.